Hubungan antara Infeksi Menular Seksual dengan Kejadian Lesi Prakanker Serviks pada Ibu Rumah Tangga di Puskesmas Sangkrah Surakarta - Dirk, Bela; Sunaryo, Rustam; Putranto, R.P. Andri (Nexus Kedokteran Komunitas, 2013)
Background: The housewife is a group of women who are at risk for sexually transmitted infections. Sexually transmitted infections is one of the risk factors for pre-cancerous cervical lesions. This study aimed to determine the relationship between the incidence of sexually transmitted infections with cervical precancerous lesions on housewife in Sangkrah health center, Surakarta Methods: This study was a descriptive cross sectional analytic approach that was conducted in June-August 2012 in Sangkrah health center, Surakarta. Sampling was done by purposive sampling technique. In this study, researchers took a sample size of 53 samples. Research carried out by filling out the questionnaire, followed by a visual inspection test checks acetic acid (VIA) and the examination of sexually transmitted infections. Where is a sexually transmitted infection is gonorrhea, candidiasis and bacterial vaginosis. Data analysis using chi-square method. Results: This study shows the value of relationship to STI: a) Gonorrhea p = 0.299, CI95% = 0.236 to 71.357, and RR = 4.10, b) Candidiasis p = 0.160, CI95% = 0.236 to 71.357, and RR = 6.29, c) Bacterial Vaginosis p = 0.117, CI95% = 0.413 to 136,271 and RR = 7.50. From the results of these data revealed that there was no relationship between the incidence of sexually transmitted infections with pre-cancerous cervical lesions housewife in Surakarta but clinically meaningless to pose the risk of precancerous cervical lesions. But found a significant relationship between STI> 1 types and cervical precancerous lesions where p = 0.000, CI95% = 1.659 to 1507.303 and RR = 50.00.   Conclusions: There is no relationship between the incidence of sexually transmitted infections (Gonorrhoea, Candidiasis, and Bacterial Vaginosis) with pre-cancerous cervical lesions on housewife in Sangkrah Health Center Surakarta. Keywords: Sexually transmitted infection, Cervical Precancerous Lesions, Housevives, Surakarta.